Evaluating the subsidence above gas reservoirs with an elasto-viscoplastic constitutive law. Laboratory evidences and case histories. (December 2021) - Musso, G.; Volonté, G.; Gemelli, F.; Corradi, A.; Nguyen, S.K.; Lancellotta, R.; Brignoli, M.; Mantica, S.
Abstract: Subsidence of hydrocarbon fields is induced by the depletion of reservoirs and connected aquifers, which causes the compaction of geologic layers. A fundamental requirement of subsidence models is then capturing the mechanical behaviour of such layers with proper constitutive laws. This paper refers to the case of two gas reservoirs from the Adriatic basin, where a time delay of subsidence with respect to production was observed. This phenomenon has been reported for other fields worldwide, also occurring when subsidence rates do not immediately vanish after the end of production. In those cases, numerical simulations based on elasto-plastic constitutive models did not provide a satisfactory match of subsidence history, even though very accurate reconstructions of pore pressure evolution were used. This motivated a further insight into the time-dependent behaviour of the sandy reservoir materials. Thus, the results of an exhaustive laboratory investigation were interpreted with an elasto-viscoplastic model from the literature, implemented by the authors in a commercial Finite Element code. The satisfactory reproduction of the experimental results proved the adequacy of the model for the materials of concern and allowed determining the parameters that were then used in the new one-way coupled field simulations. A very good agreement was finally obtained between simulation results and field monitoring data in terms of reservoir compaction, maximum settlements, settlement history and extent of the subsidence bowl. Highlights: Elasto-plastic hardening models do not always ensure proper modelling of subsidence. Oedometer tests on samples from the Adriatic evidence time dependent behaviour. An elasto-viscoplastic law is calibrated to reproduce laboratory results. The elasto-viscoplastic law was implemented in ABAQUS for field scale simulations. Case histories with measured subsidence were nicely reproduced with the elastoviscoplastic law.